Climate change policies and agendas: facing implementation challenges and guiding responses - Alves, Fátima (2020)
Climate policies are essential to mitigate climate change and to develop successful adaptation processes. However, there is a paucity of international studies that analyse the status of climate change policies. This paper reports on research undertaken in a sample of 13 highly diverse countries, in regards to their geography, socioeconomic development, vulnerability elements, adaptation, and climate-risks. The results draw attention to the global spread and standardisation of climate change policies, namely through the adoption of comprehensive National Adaptation Plans/Strategies (NAPs/NASs) that include mitigation measures and evaluation mechanisms. Although NAPs tend to take into account different non-governmental stakeholders, they are still mainly state-centred (i.e. their steering and implementation are the responsibility of each country´s Ministry of the Environment) in most of the 13 countries in which this study was carried out. The results show that NAPs’ objectives mainly reflect more a global agenda and pay less attention to national/regional vulnerabilities and contexts. In fact, despite different socioeconomic levels of development, diverse climate-risks, and dissimilar vulnerability and readiness status among countries, the examined NAPs tend to focus on the same critical sectors and objectives. Notwithstanding their similarities, our results highlight two different logics of adaptation reflected on the NAPs: one focused on economic risks and opportunities, characteristic of developed countries; and others focused on natural resources and conservation, characteristic of developing countries.